Melanoma - Current Clinical Management and Future Therapeutics 2015
DOI: 10.5772/59480
|View full text |Cite
|
Sign up to set email alerts
|

Current Insights Into Canine Cutaneous Melanocytic Tumours Diagnosis

Abstract: Cutaneous melanocytic tumours are most common in older dogs (mean age of 9 years old) [25], with a higher mean age for dogs with malignant melanocytic tumours (12 years). However, age has not been related with the patient clinical outcome and survival time [26].Although all breeds of dog (and crossbred animals) may be affected, some breeds are reported as predisposed, including Schnauzer, Doberman, Scottish Terrier, Irish Setter, Golden Retriever, Chow Chow, Cocker Spaniel, German Shepherd and Rottweiler [4,27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 131 publications
(213 reference statements)
2
10
0
Order By: Relevance
“…The tumour location was identified as an important feature of canine melanoma in our study. The oral cavity (40%‐62%) and cutaneous (27%‐31%) locations were previously reported to be the most common sites of malignant melanoma, 1,28,29 and our results indicated that the oral cavity (68%) was the most frequently affected site (Table 1). Additionally, it was surprising that the expressions of KMO and STAT3 were significantly associated with a tumour location in the oral cavity (Table 4).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The tumour location was identified as an important feature of canine melanoma in our study. The oral cavity (40%‐62%) and cutaneous (27%‐31%) locations were previously reported to be the most common sites of malignant melanoma, 1,28,29 and our results indicated that the oral cavity (68%) was the most frequently affected site (Table 1). Additionally, it was surprising that the expressions of KMO and STAT3 were significantly associated with a tumour location in the oral cavity (Table 4).…”
Section: Discussionsupporting
confidence: 69%
“…Melanocytic neoplasms have a high incidence in canines, and the most common location of canine malignant melanoma is reportedly the oral cavity 1 . Malignant melanoma is aggressive, grows rapidly, is locally invasive, and metastasizes to regional lymph nodes and distant sites, such as the lungs, heart and brain 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of equine melanocytic tumors, there is a specific feature that can be related to COX-2 expression in benign tumors. In contrast to most canine melanomas that arise de novo, equine melanocytic tumors could have a time-dependent transformation of benign into malignant tumors [ 7 ]. The presence of COX-2 in benign tumors may promote this transition to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Canine melanocytic tumors are also common, with the clinical course being related to tumor localization. Oral and mucocutaneous forms are usually highly malignant and invasive and often metastasize early in the disease course, being similar to human melanoma [ 2 , 7 , 8 ]. On the other hand, the cutaneous form more often presents a benign behavior.…”
Section: Introductionmentioning
confidence: 99%